ChemInform Abstract: Construction of Chiral Trifluoromethylated Material by Combination of Stereochemically Predictable SN2′ Reaction and Ireland—Claisen Rearrangement. Issue 46 (24th October 2013) - Ichikawa, Tomoaki; Kawasaki‐Takasuka, Tomoko; Yamada, Shigeyuki; Yamazaki, Takashi; Kubota, Toshio
Abstract The starting material is easily constructed from mandelic acid.